2022
DOI: 10.1007/s10479-022-04716-1
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting stock market volatility with a large number of predictors: New evidence from the MS-MIDAS-LASSO model

Abstract: This paper explores the effectiveness of predictors, including nine economic policy uncertainty indicators, four market sentiment indicators and two financial stress indices, in predicting the realized volatility of the S&P 500 index. We employ the MIDAS-RV framework and construct the MIDAS-LASSO model and its regime switching extension (namely, MS-MIDAS-LASSO). First, among all considered predictors, the economic policy uncertainty indices (especially the equity market volatility index) and the CBOE volatilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 99 publications
0
3
0
1
Order By: Relevance
“…We use this kind of approach to use more relevant data in order to obtain different accuracy scores in a specific range. The function f w : X ← Y is used as a self-stepping function for prediction with Φ(v i , λ) , where the age is given by λ [45]. With hyperparameter tuning, as the number of estimators is increased, the model reaches a better accuracy score, as shown in the training of their metrics.…”
Section: Key Research Findings and Recent Approaches For Cryptocurren...mentioning
confidence: 99%
“…We use this kind of approach to use more relevant data in order to obtain different accuracy scores in a specific range. The function f w : X ← Y is used as a self-stepping function for prediction with Φ(v i , λ) , where the age is given by λ [45]. With hyperparameter tuning, as the number of estimators is increased, the model reaches a better accuracy score, as shown in the training of their metrics.…”
Section: Key Research Findings and Recent Approaches For Cryptocurren...mentioning
confidence: 99%
“…Большое количество работ российских и зарубежных авторов посвящено математическому моделированию волатильности и прогнозированию фондовых рынков [9][10][11][12]. Причем многие исследователи применяют модели группы GARCH, ARFIMA и HAR, все чаще появляются исследования, доказывающие преимущества гибридных моделей с использованием нейросетей.…”
Section: Introductionunclassified
“…As such, these models hold promise for improving the accuracy and generalizability of multivariable predictions of fear extinction. Ridge Regression, Lasso Regression, and Elastic Net Regression (ENR) are three commonly used penalized regression models that have advanced the clinical research in other domains [ 65 , 66 , 67 ]. In a study of depression treatment outcomes, each was found to be more accurate than traditional Ordinary Least Squares (OLS) regression in both a training sample and separate holdout sample [ 11 ].…”
Section: Introductionmentioning
confidence: 99%